Re-creation of site-specific multi-directional waves with non-collinear current. (15th March 2018) - Draycott, S.; Noble, D.R.; Davey, T.; Bruce, T.; Ingram, D.M.; Johanning, L.; Smith, H.C.M.; Day, A.; Kaklis, P.
Abstract: Site-specific wave data can be used to improve the realism of tank test conditions and resulting outputs. If this data is recorded in the presence of a current, then the combined conditions must be re-created to ensure wave power, wavelength and steepness are correctly represented in a tank. In this paper we explore the impacts of currents on the wave field and demonstrate a simple, effective methodology for re-creating combined wave-current scenarios. Regular waves, a parametric unidirectional spectrum, and a complex site-specific directional sea state were re-created with current velocities representing 0.25, 0.5, and 1.0 m/s full scale. Waves were generated at a number of angles relative to the current, providing observations of both collinear and non-collinear wave-current interactions. Wave amplitudes transformed by the current were measured and corrected linearly, ensuring desired frequency and wavenumber spectra in the presence of current were obtained. This empirical method proved effective after a single iteration. Frequency spectra were within 3% of desired and wave heights normally within 1%. The generation-measurement-correction procedure presented enables effective re-creation of complex wave-current scenarios. This capability will increase the realism of tank testing, and help de-risk devices prior to deployment at sea. Highlights: Importance of measuring current for wave resource assessment and testing highlighted. Various wave-current scenarios simulated and measured in the circular FloWave basin. Effective generation-measurement-correction procedure implemented with low errors. Demonstrated with regular waves, parametric and non-parametric directional spectra. Mean direction to current altered providing non-collinear wave-current observation.